The contribution of Foraminifera (Family Calcarinidae) to carbonate beaches and their distribution on the coral reef flats fringing the coast of Matabungkay, Batangas - Jordan, Johannah Camille J. (Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2016)
The Philippines has many carbonate beaches that are typically associated with coral reefs. These beach systems not only provide critical habitats to endangered animals but also play a major role in tourism, recreation, and human settlements.Many of these beaches have abundant foraminiera sand, however, they are experiencing the problem of erosion or the landward retreat of the shoreline due to land loss. Erosion results mainly from a deficit in sediment supply, and therefore, sources of sediments and the modes of transport must be investigated to determine their vulnerability to impacts of sea level rise and increase in storminess. In this study, surface sediments were collected from the caronate beaches southwest of Talim Point in Matabungkay, Batangas, and analyzed for benthic foraminifral hanatocoenoses. The reef flat was surveyed and sampled for substrate and submerged vegetation (seagrass and macroalgae) to identify the preferred habitats of the dominant foraminifera. A bathymetric survey was conducted to determine the reef profile. Shorelines were traced from maps, satellite images and actual field surveys to document the changes in shoreline position. Foraminiferal test comprised 43% of the beach sand in Matabungkay. The coral-reef associated coast in Matabungkay has been fairly stable for the past 30 years. This implies that the production of sediments has been sufficient and has been continually supplied to the beach. Coastal modifications however, often improperly placed and inappropriately designed, hence disrupting the depositional process and instead exacerbate erosion, may be detrimental to the integrity of the beaches.